Planting time and mulching effect on onion development and seed production - Anisuzzaman, M.; Md Ashrafuzzaman,; Ismail, Mohd Razi; Uddin, Md. Kamal; Rahim, M. A. (Academic Journals, 2009)
A field experiment was conducted to evaluate effects of planting time and mulches on bulb growth and seed production of onion (Allium cepa L.) cv. Taherpuri. Planting time and mulches had significant influence on almost all parameters studied. Onion planted on 21 November had better agronomic traits contributing towards yield formation. Growth and seed production was accelerated by black polythene. Seed yield (460.81 kgha-1) was highest in the plots planted on 21 Nov. Seed yield was 529.06 kgha-1 where black polythene mulch was used.